2020
DOI: 10.1021/acs.jpca.9b10238
|View full text |Cite
|
Sign up to set email alerts
|

Electron Density Difference Analysis on the Oxidative and Reductive Quenching Cycles of Classical Iridium and Ruthenium Photoredox Catalysts

Abstract: In this study a detailed scrutiny of the electronic structure changes during the redox events of the oxidative and reductive quenching cycles of the representative homoleptic and heteroleptic octahedral iridium [Ir­(bpy) x (ppy)3–x ] x+ (x = 0, 1, 2, and 3) and ruthenium [Ru­(bpy) x (ppy)3–x ] x−1+ (x = 1, 2, and 3) photoredox catalysts is provided through the corresponding electron density difference Δρ­(r) distributions. The systematic analysis of the Δρ­(r) distributions provides intuitive insights into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 68 publications
1
28
0
Order By: Relevance
“…The overall agreement between experimental and simulated values (within 0.2 V) corroborates our protocol for the realistic simulation of wavefunctions (employed for the EOS analysis) and modeling solution-state energetics based on the combination of the TPSSh functional and SMD solvation method. 78,79 It has been repeatedly shown that the meta-GGA hybrid TPSSh functional can capture the main characteristics of redox events of transition metal complexes in terms of electronic structures and energy changes. 56,78−81 Furthermore, recent computational studies have also pinpointed the superior performance of TPSSh in modeling the reduction potentials of several compounds, 82−84 and it was considered among the 20 bestperforming functionals for barrier heights and binding energies from more than 200 functionals tested.…”
Section: Effective Oxidation State Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The overall agreement between experimental and simulated values (within 0.2 V) corroborates our protocol for the realistic simulation of wavefunctions (employed for the EOS analysis) and modeling solution-state energetics based on the combination of the TPSSh functional and SMD solvation method. 78,79 It has been repeatedly shown that the meta-GGA hybrid TPSSh functional can capture the main characteristics of redox events of transition metal complexes in terms of electronic structures and energy changes. 56,78−81 Furthermore, recent computational studies have also pinpointed the superior performance of TPSSh in modeling the reduction potentials of several compounds, 82−84 and it was considered among the 20 bestperforming functionals for barrier heights and binding energies from more than 200 functionals tested.…”
Section: Effective Oxidation State Analysismentioning
confidence: 99%
“…Using electron density difference analysis on the oxidative and reductive quenching cycles, we have also noted the delocalized nature of the ligands-hosted charge in homoleptic complexes such as 1. 78 When going from ruthenium homoleptic species 1 and 2 to heteroleptic complexes 3−6, the most intuitive insight gained through the EOS analysis is the localization of the ligandcentered charge into the redox-active ligand(s) (green in Figure 3) without the participation of the "spectator" (blue) ligands. Two redox active ligands can act cooperatively to temporarily store the electron in the T 1 and D red states, for example, in two bpy-s in 4, or the ligand-centered extra electron can be confined to only one redox active ligand, for example, as in the case for bpy of 6.…”
Section: Effective Oxidation State Analysismentioning
confidence: 99%
“…The above model constructed under the principle of data envelopment analysis is a very effective method in dealing with economic problems with multiple input parameter variables and multiple output parameter variables. In the usual econometrics and other economic field problems, it is difficult to draw a frontier that is consistent with the actual situation [6][7]. The reason is that this method can consider few output variables at the same time in the processing process, and treats the effective decision-making unit and the non-effective decision-making unit as the same concept.In terms of design, the advantage of DEA is that it can handle multiple items, especially multiple production problems.…”
Section: Data Envelope Analysismentioning
confidence: 99%
“…Recent computational studies have revealed the localization of electron density at the bipyridine ligand of heteroleptic [Ir(ppy) 2 (bpy)] + and the high delocalization of charge among three bipyridine ligands in homoleptic [Ru(bpy) 3 ] 2+ during the ligand-centred photoredox processes. 22 We speculated that the different electronic structure changes upon photo-excitation of the [Ir(ppy) 2 (bpy)] + moiety of SPhos-PC2 and [Ru(bpy) 3 ] 2+ moiety of SPhos-PC3 could influence the spatial disposition of a-amino radical formation. Indeed, further investigation led to the discovery of SPhos-PC3 as a highly reactive and regioselective catalyst.…”
mentioning
confidence: 99%
“…We subsequently surveyed a broad spectrum of N-aryl tetrahydroisoquinolines. Substrates incorporating various groups on the N-aryl moiety, irrespective of their electronic properties and substituent patterns, all participate in the C-H allenylation reaction, delivering allene products in 54-73% yield (22)(23)(24)(25)(26)(27)(28). To our delight, a C(sp 2 )-Cl bond was well tolerated (24), although the C(sp 2 )-Br analogue failed to undergo the reaction.…”
mentioning
confidence: 99%